System implementation of scientific developments of agricultural science in ukrainian lands from apothecary gardens to kolkhoz experimental stations (XVIII century – 50’s of the XXth century) - Vergunov, V. A. (History of science and technology, 2017)
The prerequisites of introduction and realization of demonstrative and collective experiences, ranging from the XVIII century to the early 60’s of the last century primarily on Ukrainian lands were considered on a wide historiographical basis. The formation and improvement of organizational forms, that led to the emergence of the so-called collective farm research work in March 1934, primarily, to meet the needs of the collective and state farms construction in the USSR were disclosed through the course of legislative decisions. There have been revealed their most famous achievements in the field of agricultural science. It is proved, that the methodological basis for activity of the original organizational structure of kolkhoz research work – houses- laboratories in the pre-war period, was a broad study of capabilities of the theory of vernalization developed by T.D. Lysenko, and in the 50’s XX century - systems of cultivation by T.S. Maltsev’s method through collective farm research stations set up in all regions of Ukraine. The contribution of some prominent scholars in the development of organizational approaches and later in theorizing and deployment introduction of the latest achievements of domestic agricultural science under different systems of government was highlighted. A periodization of the evolution of institutional framework of collective experimentation is proposed.